PRESUPUESTOS FILOSÓFICOS PARA UNA CONCEPCIÓN DEL DERECHO EN LA OBRA DE ALBERT CAMUS: ETAPA DE LA NEGACIÓN (2016)
Throughout the article the philosophical assumptions necessary for the construction of a conception of law are analyzed from the work of Albert Camus. Thus two tasks: first, an approach to the concepts of philosophy and philosophy of law; second, an analysis of the stage of denial or the absurd, where special attention to the Myth of Sisyphus and The Stranger is provided. The method used in the article is documentary. The validity of Camusian thought in the field of ethics and political philosophy, to find the germ of a conception of law able to problematize around various themes of the philosophy of law.